1997
DOI: 10.1007/s004250050123
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes for lipolysis and fatty acid metabolism in different organelle fractions from rape seed cotyledons

Abstract: This study addresses the still open question of whether or not in oily storage tissues, e.g. cotyledons of germinating rape (Brassica napus L.) seedlings' lipase (triacylglycerol acylhydrolase, EC 3.1.1.3) and the b-oxidation system of fatty acids are located in one or more membrane-bounded organelles. The organelles were isolated carefully and identi®ed by marker-enzyme activities. Activities of neither lipase nor acylester acylhydrolase (EC 3.1.1) could be detected either in glyoxysomes or in mitochondria, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In contrast, mammalian mitochondria are capable of complete oxidization of fatty acids to acetyl-CoA (8); the first step of fatty acid ␤-oxidation is accomplished by long-, medium-, and shortchain acyl-CoA dehydrogenases, and electrons generated by the dehydrogenases are transferred to the mitochondrial respiratory chain. By analogy, Thomas and co-workers (9 -11) have postulated the existence of plant mitochondrial ␤-oxidation, but the presence of acyl-CoA dehydrogenase was not investigated or not detected (12). In contrast, data reported by Gerhardt and co-workers (13)(14)(15) have suggested that glyoxysomes in plants can completely metabolize fatty acids to acetyl-CoA.…”
mentioning
confidence: 70%
“…In contrast, mammalian mitochondria are capable of complete oxidization of fatty acids to acetyl-CoA (8); the first step of fatty acid ␤-oxidation is accomplished by long-, medium-, and shortchain acyl-CoA dehydrogenases, and electrons generated by the dehydrogenases are transferred to the mitochondrial respiratory chain. By analogy, Thomas and co-workers (9 -11) have postulated the existence of plant mitochondrial ␤-oxidation, but the presence of acyl-CoA dehydrogenase was not investigated or not detected (12). In contrast, data reported by Gerhardt and co-workers (13)(14)(15) have suggested that glyoxysomes in plants can completely metabolize fatty acids to acetyl-CoA.…”
mentioning
confidence: 70%
“…This catabolism in higher plants proceeds primarily by peroxisomal ␤-oxidation (Cooper andBeevers, 1969a, 1969b;Gerhardt, 1985), in contrast with mammalian tissues where ␤-oxidation takes place in both peroxisomes and mitochondria. Thus, the existence in higher plants of an additional mitochondrial ␤-oxidation system is often considered controversial (Gerhardt et al, 1995;Hoppe and Theimer, 1997). It is well established that the massive degradation of fatty acids during early growth of fatty seeds proceeds through glyoxysomal ␤-oxidation (Cooper andBeevers, 1969a, 1969b;Hoppe and Theimer, 1997).…”
mentioning
confidence: 99%
“…Thus, the existence in higher plants of an additional mitochondrial ␤-oxidation system is often considered controversial (Gerhardt et al, 1995;Hoppe and Theimer, 1997). It is well established that the massive degradation of fatty acids during early growth of fatty seeds proceeds through glyoxysomal ␤-oxidation (Cooper andBeevers, 1969a, 1969b;Hoppe and Theimer, 1997). However, studies of the catabolism of branched-chain amino acids, in which the isobutyryl-CoA, 2-methyl-butyryl-CoA, and isovalerylCoA catabolites of Val, Ile, and Leu, respectively, undergo ␤-oxidation, have led Gerbling and Gerhardt (1989) to hypothesize the existence of extra-peroxisomal ␤-oxidation for Leu and Val degradation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…therein;Dieuaide et al 1993;Gerhardt et al 1995;Hoppe and Theimer 1997). Restriction of the b-oxidation activity to peroxisomes in higher plants implies that the peroxisomes are able to degrade completely longchain fatty acids to their constituent acetyl units.…”
Section: Introductionmentioning
confidence: 98%